1983
DOI: 10.1002/1097-0142(19830115)51:2<327::aid-cncr2820510227>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of specific γ-GTP isoenzyme in patients with hepatocellular carcinoma

Abstract: The authors evaluated specific γ‐GTP isoenzyme (specific γ‐GTP) found in sera of patients with hepatocellular carcinoma (HCC). In addition to band II and II' which had been reported in our previous publication, band I' also had a high specificity for HCC. One or more of these bands were detectable in 109 (55%) of 200 patients with HCC, but only in seven (3%) of 279 patients with other hepatobiliary diseases. Specific γ‐GTP was found in 38% of HCC patients with alpha‐fetoprotein (AFP) levels below 400 ng/ml. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…Other researchers used polyacrylamide gel gradient electrophoresis to fractionate one to three bands of GGT specific for hepatoma with a positivity rate of only 27 -63% (Hetland et al, 1975;Kojima et al, 1980;Sawabu et al, 1983;Kew et al, 1984). In 1985, Xu reported that they had fractionated nine to 11 activity bands of GGT adopting the method of vertical slab stage electrophoresis on polyacrylamide gel (Xu et al, 1985), in which GGTII was found in the sera of all patients with hepatoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers used polyacrylamide gel gradient electrophoresis to fractionate one to three bands of GGT specific for hepatoma with a positivity rate of only 27 -63% (Hetland et al, 1975;Kojima et al, 1980;Sawabu et al, 1983;Kew et al, 1984). In 1985, Xu reported that they had fractionated nine to 11 activity bands of GGT adopting the method of vertical slab stage electrophoresis on polyacrylamide gel (Xu et al, 1985), in which GGTII was found in the sera of all patients with hepatoma.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, other methods have been used, that is, separation of GGT bands by means of starch gel (Orlowski and Szczeklik, 1967), cellulose acetate (Hitoi et al, 1984), agarose gel (Hetland et al, 1975), polyacrylamide gel electrophoresis (Kojima et al, 1980;Suzuki et al, 1981;Sawabu et al, 1983;Kew et al, 1984), and polyacrylamide stage gel plate (Xu et al, 1985). The polyacrylamide stage gel plate method allows detecting positivity up to 90% in hepatoma patients (Xu et al, 1985).…”
mentioning
confidence: 99%
“…Alternative or additional markers having no 'falsenegative' or 'false-positive' results or else being present when xFP is either normal or is present in the non-diagnostic range, are still being sought. Studies in Japanese patients have suggested that novel 'tumour-associated' isoenzymes of y-GT might serve as a marker of HCC (Kojima et al, 1980;Sawabu et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…This exact parallel in behaviour with a-foetoprotein (aFP), a known carcinoembryonic glycoprotein and a useful serum marker of human HCC (Kew & Newberne, 1982), suggested that y-GT too might have carcinoembryonic characteristics, and that a foetal isoenzyme might be produced and secreted by human HCC tissue and serve as an additional marker of this tumour. Indeed, tumourassociated (or novel) isoenzymes of y-GT have recently been demonstrated in the serum of a proportion of Japanese patients with HCC (Kojima et al, 1980;Sawabu et al, 1983). The purpose of the present study was to determine the frequency with which tumour-associated isoenzymes of y-GT occur in HCC in another population which has a high incidence of this tumour, namely southern African Blacks, and to assess the diagnostic value of these isoenzymes in comparison with cxFP.…”
mentioning
confidence: 95%
“…Adult hepatic GGT can be induced by glucocorticoids in rats (13), chronic alcoholism in humans (14), and carcinogens and drugs (15)(16)(17). GGT levels are also increased in the mammary gland during lactation and in rat uterus during the decidual response (18,19).…”
mentioning
confidence: 99%